THE RANK METHOD AND DIRECT ASSESSMENT OF FACTORS AFFECTING THE ACTIVITY OF STUDENTS - G. R. Zmanovsky; O. V. Myasoutov (Современная наука и инновации)
The article is devoted to the consideration of methodological approaches to identifying and evaluating factors that influence the activity of modern students. In modern sociology, as a rule, the general theoretical problems of youth and youth policy are analyzed. Actively conducted empirical research in the framework of youth issues is aimed at collecting statistical data, as well as studying various aspects of the state of youth. The subject of this research is new approaches and methods to the study the factors of social and political activity of students. The research is based on the methodology of a comprehensive approach: system, political and sociological analysis, methods of expert assessments, in particular, the rank method , structural-functional and factor analysis. The article presents the main conclusions based on the results of socio-political research of the student environment of the faculty of history of the Krasnoyarsk State Pedagogical University named after V.P. Astafiev. The analysis of empirical data obtained as a result of a questionnaire survey of students allows us to identify factors that affect their activity in the socio-political space, and formulate proposals for adjusting the methodology of working with modern students.